Banking industry performance in the wake of the global financial crisis - Bhimjee, D.; Ramos, S.; Dias, J. G. (International Review of Financial Analysis, 2016)
This paper analyzes the performance of the banking industry both prior to and during the global financial crisis (GFC). Through the application of a panel regime-switching model designed to capture heterogeneity, our findings suggest that global banking performance can be grouped into two distinctive clusters, each with its own specific regime dynamics. Before the crisis, a cluster of banking institutions pertaining to advanced economies stood out for its buoyant stock market performance, whereas a second cluster, mainly composed of banking indexes that belong to emerging economies, exhibited a more subdued performance. Further, this differentiation was accompanied by low regime synchronization between the clusters. During the crisis, banking institutions behaved similarly, regime synchronization increased, and the differences in the regime dynamics vanished. Finally, the GFC constituted a highly synchronized and systemic extreme financial event, as evidenced by our findings depicting the onset of severe underlying international financial contagion processes.